Membaca Kelahiran Simbol Publik: Refleksi Semiotika dan Kekuasaan Makna Pada Maskot Pemilihan Kepala Daerah - Alhaq, Muh. Nato; Sunubi, Wahyuddin; Lalangi, Wa Ode Amatyi Rachyima (Program Studi Desain Komunikasi Visual. Fakultas Arsitektur dan Desain Jalan Raya Rungkut Madya, Gn.Anyar, Surabaya, Jawa Timur 60294, 2025)
This qualitative research examines the dynamics of the birth of public symbols of the Regional Elections through semiotic (Peirce) and social (Bourdieu) studies. The goal is to understand the birth process, meaning, and legitimacy of visual signs, as well as how symbolic power shapes legitimate meaning. Interview data was collected from designers, KPU, judges, and regional figures, focusing on institutional mechanisms and cultural interventions. The results show that the birth of mascots is dominated by administrative and aesthetic factors, ignoring the epistemic dimension (cultural/historical research). This inequality creates a dislocation of meaning, reducing the symbol of unity to a single ethnic representation. The intervention of cultural judges saves meaning by returning the mark to its local roots. Theoretically, symbols are born from the negotiation of artistic, institutional, and cultural capital, legitimized by symbolic power (Bourdieu). The research recommends the ethics of the birth of public symbols: integration of cultural research, epistemic validation, and cross-disciplinary collaboration so that symbols become moral actions and valid social representations.